Pengaruh Melek Finansial, Sosialisasi Orang Tua, dan Teman Sebaya Terhadap Perilaku Menabung Mahasiswa Bidik Misi Fakultas Ekonomi Universitas Samudra - Suri Amilia; Tengku Putri Lindung Bulan; Muhammad Rizal (Jurnal Samudra Ekonomika, 2018)
The objective of the research was to find out the financial literacy, socialisation of parents,and peers influence of the saving behaviour of bidikmisi students on Fakultas Ekonomi - Universitas Samudra. Data collection techniques were conducted by distributing questionnaires with a Likert scale with the number of respondents as many as 197 people. Data analysis method using multiple linear regression, with multiple linear regression analysis equation in research are: Y = 12, 388 + 0,244X1 + 0,436X2 + 0,074X3. The value of Adjusted R Square obtained by 0,28 or 28% indicates the ability of financial literacy variables, socialisation of parents, and peers, in explaining the saving behaviour of 32,8%, while the remaining 72% is influenced by other factors not researched. Significant value for financial literacy is 0,002 < alpha 0,05, financial literacy variable have a significant effect of the saving behaviour, and the hypothesis accepted. Significant value for a socialisation of parents 0,000 < alpha 0,05, Variables of socialisation of parents significantly influence of the saving behaviour. Thus the hypothesis accepted. Significant value for peers of 0,380 > alpha 0,05, Peer variables significantly influence of the behaviour saving. Thus the hypothesis is rejected.